Challenges and Strategies of Senior High School Principals in Facing Curriculum Transition - Kaharuddin, Kaharuddin; Annajmi, Annajmi; Amiri, Ahabbi Rachman Al; Darmansyah, Rafik; Deswandi, Ramadhan; Azwir, Azwir (Al-Qalam Institue, 2025)
This study aims to identify the main challenges faced by principals in managing the curriculum transition in senior high schools and the strategies implemented to overcome these obstacles. The implementation of the Independent Curriculum requires significant adaptation for principals and educators, especially in terms of understanding and implementing changes that include more independent and project-based learning management. The research method used is a qualitative approach with a case study method, where data is collected through in-depth interviews with principals, teachers, and school supervisors. Purposive sampling technique was applied to select informants who have direct experience in implementing the Independent Curriculum. Data analysis was carried out thematically with a source triangulation approach to increase the validity of the research results. The findings of this study indicate that the main challenges lie in teacher understanding and infrastructure readiness, while the strategies implemented include intensive training and clear division of roles between educators. Evaluations and recommendations from school supervisors also provide important contributions in assessing the success of curriculum implementation. The contribution of these findings is expected to be a reference for education policies in optimizing curriculum transition in Indonesia.